2022
DOI: 10.1007/s10826-022-02292-3
|View full text |Cite
|
Sign up to set email alerts
|

Listen to the Children: Elementary School Students' Perspectives on a Mindfulness Intervention

Abstract: In recent years, mindfulness-based practices in grade schools have been associated with students’ improved cognitive skills and general classroom behavior. In the majority of studies, however, only teacher and parent feedback are elicited, omitting a considerably significant voice – that of the students. Our study aims to fill this gap by exploring student opinions and perceptions regarding the implementation of a classroom-based mindfulness program. Elementary school students (N = 51) took part in teacher-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, as Jackson et al (2010) reported, self-report measures provide a reading of resilience at a particular point in time that could be affected by events occurring in the youth’s life at that moment. Certainly, the mixed methods approach enabled us to more fully understand the young people’s experiences of the intervention, and their voices are crucial in helping us understand the types of MBIs that can provide benefits for them (D'Alessandro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Jackson et al (2010) reported, self-report measures provide a reading of resilience at a particular point in time that could be affected by events occurring in the youth’s life at that moment. Certainly, the mixed methods approach enabled us to more fully understand the young people’s experiences of the intervention, and their voices are crucial in helping us understand the types of MBIs that can provide benefits for them (D'Alessandro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The goals of MBIs usually include becoming more aware of one’s moment-to-moment stream of consciousness and to accept these experiences without judgment. There is emphasis on improving attention and empathy, as well as building emotion regulation and self-awareness (D'Alessandro et al, 2022). MBIs with young people show a wide range of promising benefits ranging from emotion regulation (Schussler et al, 2021; Zhang et al, 2022), enhancing executive functioning (Lu et al, 2021), lowering feelings of anxiety (Borquist-Conlon et al, 2019; Moyes et al, 2022), and improving social competence, emotional resilience (Culang et al, 2021), mood, and relationships (Dai et al, 2022; Van Vliet et al, 2017).…”
mentioning
confidence: 99%
“…The perception of participants is a key factor in validating integrative approaches, which are difficult to assess with quantitative tools, especially in the context of an innovative hypothesis for which there are no dedicated standardized validated questionnaires. Mindfulness is a subtle approach for which focus group analysis seems relevant, although a few qualitative studies have been conducted to date, for example, in online mindfulness, 28 , 29 mindfulness at school, 30 in surgeons, 31 , 32 and schizophrenic patients. 33 The qualitative approach was found to be effective to identify important areas for further studies in people with cancer and to test the feasibility and acceptability of mindfulness-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness has been studied in different areas, such as its application in virtual reality for promoting mindfulness practice, its influence on relationship satisfaction among couples, its involvement in programs for adolescents, and its efficacy in university students (Tan, 2015;Navarro-Haro et al, 2017;Chung et al, 2022;D'Alessandro et al, 2022). In addition, mindfulness has been examined in the context of physical activity, stress reduction, depressive symptoms, and self-injury involvement (Cruz, 2015;Kennedy & Resnick, 2015;Carletto et al, 2016;Feliu-Soler et al, 2016;Dash et al, 2022).…”
Section: Introductionmentioning
confidence: 99%